Drug Targeting of Genomic Instability in Multiple Myeloma - Beksac, Meral; Balli, Sevinc; Akcora Yildiz, Dilara (Frontiers in Genetics, 2020)
Genomic instability can be observed at chromatin and chromosomal level. Instability at macro or micro level includes either centrosome abnormalities (CA) resulting in numerical plus structural chromosomal changes or defects in DNA repair pathways resulting in microsatellite instability (MIN) or mutations. Genomic instability may occur during carcinogenesis without hampering the cancer cell survival and growth, a dilemma not solved yet. Solid tumors arising from most cells of epithelial origin are known to possess high grade of genomic instability rendering resistance to chemotherapy and radiotherapy. A high score based on genes of DNA repair and observed among 25 % of myeloma patients has been shown to be highly prognostic, independent from ISS. However, a biomarker of DNA repair defect: loss of heterozygosity (LOH) was observed less frequently (only 5 %) among newly diagnosed patients. The good news is that, many new molecules targeting the pathways involved in genomic instability are under development and some of them have already entered clinical trials. Many PARP inhibitors have received FDA approval in BRCA1 mutated /metastatic breast cancer, ovarian, lung cancer therapy. Topoisomerase, epigenetic histone modification targeting inhibitors such as HDAC (Histone deacetylase) inhibitors have been reported to have novel therapeutic implications against genomic instability. Several of the small molecule inhibitors targeting chromosomal level instability such as PARP, Akt, Aurora kinase, cyclin dependent kinase or spindle kinase inhibitors have been tested in mouse models and early phase I/II trials. ATM, ATR kinase inhibitors, DNA helicase inhibitors are drugs that are emerging as promising novel agents. However, most of these drugs are not effective as monotherapy but act in strong synergism when combined with DNA damaging agents ie radiotherapy, platin derivatives, immunomodulators or proteasome inhibitors. In this review, new inhibitory drugs targeting genomic instability and their mechanisms of action will be discussed.